Determination of financial literacy, financial inclusion, and access to financing on the performance of small and medium enterprises in wajo regency - Jaya, Asrul (International Journal of Applied Finance and Business Studies, 2025)
This study aims to determine and analyze the influence of financial literacy, financial inclusion, and access to financing on the performance of MSMEs in Wajo Regency. This is a quantitative associative study, which aims to determine the relationship or influence between two or more variables. A quantitative approach was used to test the hypothesis through statistical data processing. The research was conducted on SMEs located in Wajo Regency, South Sulawesi Province. The sample used in this study consisted of 93 respondents. Data collection was carried out using questionnaires, documentation, and literature review. Data analysis techniques using SPSS version 26 for Windows include: 1) instrument testing consisting of validity and reliability tests; 2) classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests. Data analysis was performed using multiple linear regression with SPSS version 26 for Windows. The hypothesis testing used was the t-test and determination. Based on the results of the data analysis, it was found that the variables of financial literacy (P-value 0.002<0.05), financial inclusion (P-value 0.013<0.05), and access to financing (P-value 0.000<0.05) have a positive effect on the performance of MSMEs in Wajo Regency.